Differential molecular signatures in response to CD19-CAR T cell therapy compared with conventional pharmacotherapy in systemic lupus erythematosus - Garantziotis, Panagiotis; Beretta, Lorenzo; Lindblom, Julius; Moysidou, Georgia Savina; Nikolopoulos, Dionysis; Grieshaber Bouyer, Ricardo; Hagen, Melanie; Bergmann, Christina; Wirsching, Andreas; Bozec, Aline; Schneider, Matthias; Barturen, Guillermo; et al. (Annals of the Rheumatic Diseases, 2025)
Objectives: Early trials of CD19-chimeric antigen receptor (CAR) T cell therapy in systemic lupus erythematosus (SLE) show promise, but the molecular mechanisms underlying its disease-modifying effects remain unclear. We aimed to compare biological profiles and alterations following CD19-CAR T cell versus standard pharmacotherapy in SLE. Methods: Pseudo-bulk gene expression derived from single-cell RNA sequencing of peripheral blood mononuclear cells from 7 SLE patients before and after CD19-CAR T cell therapy was compared with whole-blood transcriptome data from 30 SLE patients in remission on standard pharmacotherapy and 31 SLE patients before and 6 months after treatment with rituximab, belimumab, or cyclophosphamide. Pathway analysis was conducted using Functional Analysis of Individual Microarray Expression and gene set enrichment analysis. Results: CD19-CAR T cell-induced remission was characterised by marked suppression of complement activation, type I interferon, DNA damage response (DDR), and cell death pathways compared with remission following conventional pharmacotherapy, alongside an upregulation of lipid metabolism pathways. Compared with rituximab and belimumab, CD19-CAR T cell therapy induced greater downregulation of type I/II interferon, DDR, and chemokine pathways. Compared with cyclophosphamide, CD19-CAR T cell therapy induced greater suppression of interferon, mitochondrial, and mammalian target of rapamycin signalling pathways. Conclusions: CD19-CAR T cell therapy induces substantial suppression of key immunological pathways involved in SLE, including complement activation and type I interferon responses, accompanied by a metabolic reprogramming. Molecular profiles of remission after CD19-CAR T cell therapy differ from those induced by conventional SLE pharmacotherapy, suggesting more profound CD19-CAR T cell-induced biological alterations.
CRIS-Team Scopus Importer:2025-08-01